IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK (PJBL) UNTUK MENINGKATKAN PARTISIPASI DAN KOLABORASI PESERTA DIDIK DALAM PEMBELAJARAN DI SD NEGERI 55/I SRIDADI - Andika Samudra; Raihana Putri Eka Azri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Collaboration and participation are important elements that must be developed during the educational process. Project Based Learning is one of the learning methods that can be used to improve teamwork skills through group project activities. The purpose of this study was to determine how well the Project Based Learning paradigm works to improve student engagement and cooperation. Students of class V C of SD Negeri 55/I Sridadi were the subjects of the study. The research methodology used was collaborative Classroom Action Research (CAR) using a mixed method approach, namely a quantitative approach using questionnaires and a qualitative approach using observation and documentation. The results of the study showed that the use of the Project Based Learning paradigm can improve student engagement and cooperation. This is evidenced by the average proportion of student collaborative observations increasing by 8.14% from cycle I to cycle II. This is also supported by the results of the student collaboration questionnaire which showed an average percentage of 73.84% in cycle I and 81.96% in cycle II which is included in the very good category. Thus, it can be said that the Project Based Learning paradigm has succeeded in improving student collaboration in class V C of SD Negeri 55/I Sridadi.